Rice production using mechanized direct-seeded rice with suitable agronomic practices - Pin, Sokornthea; Then, Rathmuny; Ouk, Akhara; Laing, Alison; Flor, Rica Joy (2024)
The video series provides a simplified package of agronomic practices for rice production using mechanized direct seeding that has been tested in Cambodia. It is targeted for rice producers, and can also be useful for rice seed producers.